Factors Affecting the Timeliness of Interim Financial Reporting - Nur Hidayah Istiqomah; Oktavia Isanur Maghfiroh; Monika Yovita; Mutiara (ProBisnis : Jurnal Manajemen, 2023)
Presenting pertinent information effectively involves being timely. The interim financial reporting process is influenced by several major elements. Users of financial reports will feel more confident if the timely submission of financial reporting material is made. Based on the findings of an earlier study, identified variables that are related to the timeliness of interim financial reporting. So, the purpose of this research is to learn more about the variables that are most important and have a favorable impact on interim financial reporting timeliness. According to the study's findings the primary component namely leverage has a significant impact on interim financial reporting timeliness and a concomitantly favorable impact.